Historicising corpus stylistics: keywords and collocation in William Langland’s Piers Plowman - Cordell, Jacqueline (2019)
This study presents a uniquely interdisciplinary survey of the language in Piers Plowman. Drawing from digital methods and theories developed in corpus linguistics, this investigation examines the relationship between linguistic form and literary function in the poem’s lexis by comparing the language contained in the text to a reference corpus of contemporary late medieval narrative poetry. This comparison reveals quantitatively-established text features and patterns that, when placed within theoretical frameworks in literary linguistics, offer a point of departure for analysing aspects of the poem’s literary style with a pivotal focus on lexis addressing themes of consumption and the law. This approach does not provide a comprehensive analysis of the linguistic features contributing to the style characterising Piers Plowman, but rather operates as a case study illustrating the analytical benefits of taking a corpus approach to the poem.